2015
DOI: 10.4236/jsea.2015.810049
|View full text |Cite
|
Sign up to set email alerts
|

An E-Negotiation Agent Using Rule Based and Case Based Approaches: A Comparative Study with Bilateral E-Negotiation with Prediction

Abstract: The research in the area of automated negotiation systems is going on in many universities. This research is mainly focused on making a practically feasible, faster and reliable E-negotiation system. The ongoing work in this area is happening in the laboratories of the universities mainly for training and research purpose. There are number of negotiation systems such as Henry, Kasbaah, Bazaar, Auction Bot, Inspire, and Magnet. Our research is based on making an agent software for E-negotiation which will give … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Automated negotiation research revealed several benefits that computerized negotiation can offer to e-markets. These benefits include: (1) better deal (win-win settlement); (2) decreased transaction cost and time associated with human operation; (3) increased efficiency of settlements even for semi-structured, multi-issue business bargaining problems; and (4) minimizing of some negative aspects of human negotiation, such as avoiding face-to-face encounters with people who are uncomfortable with "bargaining" [5,16,17]. Unfortunately, a poorly designed automated negotiation agent will not be able to deal effectively with a skillful human counterpart that can adopt flexible strategies [5,17].…”
Section: Study Backgroundmentioning
confidence: 99%
“…Automated negotiation research revealed several benefits that computerized negotiation can offer to e-markets. These benefits include: (1) better deal (win-win settlement); (2) decreased transaction cost and time associated with human operation; (3) increased efficiency of settlements even for semi-structured, multi-issue business bargaining problems; and (4) minimizing of some negative aspects of human negotiation, such as avoiding face-to-face encounters with people who are uncomfortable with "bargaining" [5,16,17]. Unfortunately, a poorly designed automated negotiation agent will not be able to deal effectively with a skillful human counterpart that can adopt flexible strategies [5,17].…”
Section: Study Backgroundmentioning
confidence: 99%
“…Our main focus in this paper is on how effectively and optimally few of the existing negotiation mechanisms (bargaining-bilateral/multilateral, Bidding, Auctioning, multi strategy) can be suitably implemented with techniques like decision support systems, linear programming and form a consolidated research material on various strategies with set of rules/protocols with few assumptions. We are presenting few results and detailed analysis on a working of bilateral negotiation protocol using behavior prediction in decision support system [Bala, Vij and Mukhopadhyay (2015)]; multilateral negotiation protocol using linear programming [Vij, Patrikar, Mukhopadhyay et al (2015)]; Negotiation using Rule based and case based reasoning protocol [More, Vij and Mukhopadhyay (2015)].…”
Section: Figure 1: Classification Of Automated Negotiationmentioning
confidence: 99%